Geologi dan Potensi Terbentuknya Mineralisasi Uranium Tipe Batupasir di Daerah Hatapang, Sumatera Utara - Ngadenin, Ngadenin (EKSPLORIUM, 2013)
The Study based on geological setting of Hatapang region, North Sumatera, identified as a favourable area to the formation of sandstone type uranium mineralization. This characterized by the occurred of anomalous radioactivity, uranium contents of the upper cretaceous granite intrusions and radioactivity anomalous of tertiary sedimentary rocks deposited in terrestrial environments. The study is objectived to find out the potential formation of sandstone type-uranium mineralization within tertiary sedimentary rocks based on data’s studies of geological, geochemical, mineralogy, radioactivity of rocks. Stratigraphy of hatapang area of the oldest to youngest are quartz units (permian-carboniferous), sandstone units (upper Triassic), granite (upper cretaceous), conglomerate units (Lower –middle Miocene) and tuff units (Pleistocene). Hatapang’s granite is S type granite which is not only potential as source of radioactive minerals, particularly placer type monazite, but also potential as source rocks of sandstone type-uranium mineralization on lighter sedimentary rocks. Sedimentary rock of conglomerate units has potential as host rock, even though uranium did not accumulated in its rocks since the lack number of carbon as precipitant material and dissolved U+6 in water did not reduced into U+4 caused the uranium mineralization did not deposited.